Pyrrolizidine alkaloids from Onosma arenaria (Boraginaceae) - El-Shazly, Assem; Abdel-Ghani, Afaf; Wink, Michael (Biochemical systematics and ecology, 2003)
Uplandicine, a 1,2-unsaturated pyrrolizidine alkaloid esterified with acetyl and echimidinyl moieties at C-7 and C-9, respectively, was isolated as a major component from the alkaloid extract of Onosma arenaria. Its structure was confirmed by MS (EI and positive FAB), 1H- and 13C-NMR analysis. Furthermore, nine minor alkaloids were identified on the basis of mass spectral data and/or Kovats retention indices.
Gesehen am 04.10.2017